Ever constant - Peterson, Tracie; Woodhouse, Kimberley, 1973- (The treasures of Nome, 2022)
"On the surface, Whitney Powell is happy working with her sled dogs, but her life is full of complications that push her over the edge. When sickness spreads in outlying villages, Dr. Peter Cameron turns to Whitney and her dogs for help navigating the deep snow, and together they discover that sometimes it's only in weakness you can find strength"--